Gender Perspective on Tax Policy - Neshovska Kjoseva, Elena (Law Faculty Iustinianus Primus Skopje, 2025)
From ancient times until today, the main function of all tax systems remains unchanged. Their key purpose is to generate revenues, while equity, fairness and non-discrimination are established as fundamental principles of taxation. States use the collected tax revenues to ensure proper functioning of society and to meet essential needs of all citizens. In recent years, the demand for gender equality has emerged as a critical aspect of these needs. Tax systems are generally considered neutral, designed to impact everyone equally. All individuals and citizens are obliged to pay taxes and other public levies, as well to contribute in covering public expenditure regardless of gender, race, colour of skin, national and social origin, political and religious belief, property, and social status. Additionally, the language of the tax provisions does not mention gender in a way that would possibly impose different tax treatment between men and women. Therefore, if taxpayers earn the same income, they will be taxed the same and no one will be questioning gender (in)equity. Traditionally, tax policy is perceived from an economic point of view focusing on revenue generation and economic growth. On the other hand, the gender equality is often seen as a social issue. However, significant disparities exist between men and women in the labor market, including differences in employment status (formal vs. informal), job types, and working hours, as well as distinct consumption patterns influenced by gender roles, particularly in caregiving and household responsibilities. Recognizing these disparities, governments have begun to acknowledge the importance of gender equity and have started to implement measures that are expected to focus on gender biases within tax policies. This paper aims to: (i) explore how tax systems may accidentally perpetuate gender inequalities, and (ii) assess the extent to which states can use the tax policy as an instrument to promote and protect gender equality.